2007
DOI: 10.2174/156800907780058871
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 Viral Oncolysis and Molecular Imaging with PET

Abstract: Viral oncolysis, the destruction of cancer cells by replicating viruses, is a new modality of cancer therapy. This strategy involves use of viruses that are either genetically engineered to replicate preferentially in neoplastic cells, or use of viruses that display innate tropism for neoplastic cells. These viruses may also be modified to deliver transgenes to destroy cancer cells. While numerous viruses may be used for this form of cancer therapy, HSV-1 is an attractive vector for viral oncolysis due to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…3F). This property, which rests on the high specificity of the virus, could lead to the development of virus-mediated imaging of tumors, particularly since specific substrates of HSV thymidine kinase were designed, which enable the detection of HSV-infected cells by the non invasive, repeatable positron emission tomography (PET) [35].…”
Section: Discussionmentioning
confidence: 99%
“…3F). This property, which rests on the high specificity of the virus, could lead to the development of virus-mediated imaging of tumors, particularly since specific substrates of HSV thymidine kinase were designed, which enable the detection of HSV-infected cells by the non invasive, repeatable positron emission tomography (PET) [35].…”
Section: Discussionmentioning
confidence: 99%
“…The destruction of cancer cells by replicating viruses or viral oncolysis is currently under investigation for cancer therapy 6 . This approach is based on lytic virus replication once it infects a cancer cell.…”
Section: Oncolytic Hsv-1 As a Therapeutic Option For Meningeal Metastmentioning
confidence: 99%
“…Most commonly ganciclovir is used as prodrug in this suicide gene therapy paradigm. Molecular imaging with PET using tk as a PET reporter gene offers the desired qualities of a noninvasive test which can be easily repeated to determine the location and magnitude of viral replication and tumour lysis and has been extensively used for both preclinical and clinical studies using HSV-1 oncolytic vectors [268]. Using replication-competent HSV-1 oncolytic virus with tk under the control of different promoters, it has been demonstrated that viral infection proliferation and promoter characteristics all interact to influence FIAU accumulation and imaging [269].…”
Section: Imaging Gene Therapymentioning
confidence: 99%